Robotic-assisted versus laparoscopic versus open radical cystectomy: a systematic review and network meta-analysis of randomized controlled trials - Kowalewski, Karl-Friedrich; Wieland, Victoria; Kriegmair, Maximilian; Uysal, Daniel; Sicker, Tom; Stolzenburg, Jens-Uwe; Michel, Maurice Stephan; Haney, Caelán Max (European urology focus, 2023)
Context - Multiple randomized controlled trials (RCTs) on the three approaches of radical cystectomy (robotic assisted [RARC], laparoscopic [LRC], and open [ORC]) have been published recently. - Objective - To perform a systematic review and network meta-analysis (NMA) of RCTs comparing RARC, LRC, and ORC, with the primary outcomes being overall survival (OS) and recurrence-free survival (RFS). - Evidence acquisition - A search of the Cochrane Central Register of Controlled Trials, MEDLINE, and Web of Science (last search: 20/05/2022) was performed. The prospectively registered protocol stated that a NMA of the primary outcomes would be performed only if there was sufficient evidence to compare all three approaches. In case of insufficient evidence, a comparison between the two most common approaches would be performed. The risk of bias and certainty of evidence (CoE) via the Grading of Recommendations Assessment, Development, and Evaluation approach was assessed for direct evidence and the most common comparison. - Evidence synthesis - Ten trials were identified. There was insufficient evidence for a NMA of all approaches for the primary outcomes. The meta-analysis of RARC and ORC showed no differences in OS (hazard ratio (HR) [confidence interval (CI): 0.98 [0.73-1.30]) and RFS (HR [CI]: 0.99 [0.75-1.31]) with moderate CoE. The secondary outcomes showed lower rates of transfusions (p < 0.01) and longer operating time (p < 0.01) with high CoE for RARC compared with ORC. There were no differences for quality of life, positive margins, length of hospital stay, or major complications (all p > 0.05). - Conclusions - There are no differences in OS and RFS between RARC and ORC, with moderate CoE. Clinicians should likely apply the approach with which they can reach the highest case volume and in which they have the most experience. - Patient summary - We looked at the difference between three types (robotic assisted, laparoscopic, and open) of operating techniques for radical cystectomy. The data showed no significant differences in OS between the robotic-assisted and the open technique, while enough data were not available to make a comparison with conventional laparoscopic surgery.
Online verfügbar: 16. Dezember 2022
Gesehen am 24.10.2023